"I can go teach for 30 minutes, and then I can tell" – The risk work of teachers in Danish secondary schools. (18th August 2021) - Cecchini, Mathilde
Abstract : Based on an ethnographic study of health promotion and risk prevention in two public schools in Denmark, in this article I explore how schoolteachers carried out health risk work in the context of health promotion initiatives. I found that in order to manage the high degree of uncertainty that this kind of work entails, schoolteachers relied upon understandings of the relationship between social class, gender and ethnicity and of health outcomes which were based on their experience as well as the norms and stereotypical beliefs about the characteristics of specific social groups. This relationship between the social identities of the students and their future health took on an almost deterministic character among the teachers. Consequently, they perceived students' future health as determined by factors that were largely beyond their control, making risk work seem like an impossible task.